Application of random survival forest for competing risks in prediction of cumulative incidence function for progression to AIDS - Omid Hamid; Mahtab Tapak; Jalal Poorolajal; Payam Amini; Leili Tapak (Epidemiology, Biostatistics and Public Health)
Objective: There has remained a need to better understanding of prognostic factors that affect the survival or risk in patients with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS), particularly in developing countries. The aim of the present study aimed to identify the prognostic factors influencing AIDS progression in HIV positive patients in Hamadan province of Iran, using random survival forest in the presence of competing risks (death from causes not related to AIDS). This method considers all interactions between variables and their nonlinear effects.